2021
DOI: 10.1038/s41467-021-23611-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Coptis chinensis genome reveals the diversification of protoberberine-type alkaloids

Abstract: Chinese goldthread (Coptis chinensis Franch.), a member of the Ranunculales, represents an important early-diverging eudicot lineage with diverse medicinal applications. Here, we present a high-quality chromosome-scale genome assembly and annotation of C. chinensis. Phylogenetic and comparative genomic analyses reveal the phylogenetic placement of this species and identify a single round of ancient whole-genome duplication (WGD) shared by the Ranunculaceae. We characterize genes involved in the biosynthesis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(73 citation statements)
references
References 97 publications
3
69
1
Order By: Relevance
“…In TF prediction, the most common are WRKY, AP2/ERF-ERF ( Table S4 ), and bZIP, followed by C2H2, C3H, and bHLH; GRAS, NAC, and MYB are also commonly identified. Many of these TFs are frequently involved in the regulation of plant defense against various biotic/abiotic stresses and biosynthesis of secondary metabolites ( Liu et al, 2021 ). SSRs are widely and evenly distributed in plant genomes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In TF prediction, the most common are WRKY, AP2/ERF-ERF ( Table S4 ), and bZIP, followed by C2H2, C3H, and bHLH; GRAS, NAC, and MYB are also commonly identified. Many of these TFs are frequently involved in the regulation of plant defense against various biotic/abiotic stresses and biosynthesis of secondary metabolites ( Liu et al, 2021 ). SSRs are widely and evenly distributed in plant genomes.…”
Section: Resultsmentioning
confidence: 99%
“…Here the gene tree analysis could help resolve key evolutionary steps with regard to new BIA pathways in these plants. The current biochemical and molecular insights of BIA biosynthesis are mainly from Ranunculales species, especially Papaver somniferum , Eschscholzia californica , and Coptis species ( Lee & Facchini, 2010 ; Li et al, 2020 ; Liu et al, 2021 ). Some genes involved in the biosynthesis of BIAs have been functionally characterized, which, in conjunction with full-length Dichocarpum transcripts of this study and other homologous sequences in NCBI NR and CNGB 1KP databases, were amenable in gene tree analyses of BIA pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Almost all of the enzyme genes involved in the biosynthesis of these alkaloids have been identified and characterized, in addition to which metabolic engineering approaches have been attempted to manipulate the BIA biosynthetic pathways [ 1 ]. Furthermore, whole-genome sequencing of several BIA-producing plants such as P. somniferum , E. californica , Aquilegia coerulea , Nelumbo nucifera , Macleaya cordata , and Coptis chinensis has been performed, which provides us with more information for the identification of unknown genes involved in BIA biosynthesis [ 106 , 107 , 108 , 109 , 110 , 111 , 112 ].…”
Section: Tfs Involved In the Regulation Of Alkaloid Biosynthetic Enzyme Genes Expressionmentioning
confidence: 99%
“…To date, the number of organisms with completely known genomes in the NCBI database has now reached 60 363 species but included only 366 plants. For instance, in Ranunculaceae , only genomes of Coptis chinensis ( Coptis genus) 2 and Aquilegia coerulea ( Aquilegia genus) were publicly available in NCBI () and Phytozome () databases. Secondly, recent research studies have indicated that interspecific gene flow, also called parallel gene transfer, occurred in plants, and thus increased the possibility of polyphyly and paraphyly of plant species.…”
Section: Introductionmentioning
confidence: 99%
“…1 This hope faded as it became more and more apparent that morphological characteristics in higher plants were affected by ecological stress factors, and thus were subject to phenomena of coverage and parallel evolution. 2 With the development of molecular biology, the use of DNA data in plant taxonomy has been highly successful in many examples but has the following three limitations. Firstly, the current technologies usually used separate regions of the genome, including genomic compartments and coding regions, to analyze the phylogenetic relationship among plants due to the limited whole genome information, and thus only reveal partial instead of the entire evolutionary relationship among plants.…”
Section: Introductionmentioning
confidence: 99%